Preferensi Spodoptera Frugiperda J.E. Smith pada Berbagai Tanaman - Azwana, Azwana (Universitas Medan Area, 2021)
Spodoptera frugiperda (Lepidoptera: Noctuidae) is a pest that boomed in early 2019. The research was conducted descriptively in areas that had never been attacked by S. frugiperda by planting various types of crops such as sweet corn, white corn, hybrid corn, green beans, tomatoes, chilies and sorghum. The results showed that S. frugiperda was very fond of sweet corn, followed by white corn, hybrid corn and sorghum. Green bean, chili and tomato plants were not attacked by S. frugiperda. Pest S. frugiperda began to attack sweet corn plants at 3 weeks after planting with the initial attack in the form of scratches on the leaves and continued to the base / growing point (leaves still curled). Even this pest also attacks the male flowers that have not opened and attacks the sweet corn cobs. S. frugiperda began to attack sweet corn at the age of 20.33 days after planting, on white corn 25.67 days after planting, hybrid corn 25.53 days after planting and sorghum at 28.67 days after planting. In sweet corn, the attack reached the corn cobs, while in white corn and hybrid corn, the attack only showed damage to the leaves, not to the cornflower as well as to sorghum. The percentage of attack on white corn (22.15%) and hybrid corn (18.26%) and on sorghum was only 10.34% less than attack on sweet corn (40.02%).